Prevalence of Cowdria ruminantium infection in Amblyomma hebraeum ticks from heartwater-endemic areas of Zimbabwe - Peter, T.F.; Perry, Brian D.; O'Callaghan, C.J.; Medley, G.F.; Mlambo, G.; Barbet, A.F.; Mahan, S.M. (Cambridge University Press, 1999)
Analysis of the transmission dynamics of Cowdria ruminantium, the tick-borne rickettsial agent of heartwater in ruminants, requires accurate measures of infection in vector populations. To obtain these, Amblyomma hebraeum ticks were collected at two heartwater-endemic locations in the lowveld and highveld regions of Zimbabwe and assessed for C. ruminantium infection with specific polymerase chain reaction (PCR) and DNA probe detection assays. At the lowveld site, 11±2% (50}446) of adult ticks and 8±5% (23}271) of nymphs carried C. ruminantium, as detected by PCR. At the highveld site, the prevalence of infection in adult ticks was 10±2% (40}392). DNA probe analysis revealed that most infections at both sites were of low intensity ; only 9% and 23% of all nymph and adult tick infections, respectively, were greater than 70000 organisms, the detection limit of the DNA probe. However, the majority (70%) of probedetectable adult tick infections were high, between 10( and 10* organisms}tick, while those within nymphs were lower, between 10& and 10' organisms}tick.